Code Switching Types Used by Lecturers - Syilvia Wenny J (IJET (Indonesian Journal of English Teaching), 2018)
It became one phenomenon occurred when lecturer changed one language (L1) into other language (L2) in one utterance. This was one kind of bilingualism named code switching. On this study, it focused on the types of code switching used by English lecturers in STIE Muhammadiyah Jambi. The objective of this study was to identify the types of code switching used by English lecturers. This was descriptive research. The participants were four English lecturers who taught English I for the first semester students at STIE Muhammadiyah Jambi. There were 2 meetings for each class to be recorded their teaching activity and also analyzed. After analyzing, it was found that there were three main types of code switching which were tag switching, inter-sentential and intra-sentential. In inter-sentential code witching it was divided into 2 sub type which were metaphor and situational code switching. The percentages of those types were 21.54% of tag switching, 33.07% of metaphor,16.15% of situational (or 49.22% of inter-sentential), and 29.23% of intra-sentential. Based on those data, it could be concluded that metaphor of inter-sentential code switching is the highest type used by lecturers. It happened because the lecturers tend to emphasis on learning purpose.